2013
DOI: 10.1016/j.canlet.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TGF-β signaling in combination with TLR7 ligation re-programs a tumoricidal phenotype in tumor-associated macrophages

Abstract: Inadequate immunity that occurs in a tumor environment is in part due to the presence of M2-type tumor-associated macrophages (TAMs). TGF-β has a multi-functional role in tumor development including modulating the biological activity of both the tumor and TAMs. In this study, using an in vitro TAM/tumor cell co-culture system ligation of TLR7, which is expressed on TAMs but not the tumor cells, in the presence of TGF-β receptor I inhibitor re-programmed the phenotype of the TAMs. In part they adopted the pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 34 publications
0
31
0
1
Order By: Relevance
“…Supportingly, results of luciferase assays showed that TGF-β enhanced the Tim-3 promoter activities (figure 5D). Considering the active involvement of macrophages in many TGF-β-related diseases,30 31 our data here highlight the potential role of Tim-3 in multiple pathological conditions by regulating macrophage functions.…”
Section: Discussionmentioning
confidence: 58%
“…Supportingly, results of luciferase assays showed that TGF-β enhanced the Tim-3 promoter activities (figure 5D). Considering the active involvement of macrophages in many TGF-β-related diseases,30 31 our data here highlight the potential role of Tim-3 in multiple pathological conditions by regulating macrophage functions.…”
Section: Discussionmentioning
confidence: 58%
“…1D). Furthermore, NFSA-CM induced much higher expression of CD80, the well-established M1-macrophage marker (18), in RAW264 cells than did MS-K-CM (Fig. 1E).…”
Section: Resultsmentioning
confidence: 94%
“…But generally, results with anti-TGF-β antibodies have been disappointing to date, and TGF-β-neutralizing antibodies may have adverse effects in normal healthy tissues. Ligation of Toll-like receptor 7, which is expressed on TAMs, but not tumor cells, in the presence of TGF-βRI inhibitor, reprogrammed the phenotype of the TAMs to M1-type with increased tumoricidal activity and elevated expression of iNOS, CD80, and MHC class II, whereas TGF-β secretion was reduced ( 11 ). This combination also increased tumor apoptosis and elevated the number of CD4 + , CD8 + , and CD19…”
Section: Cd4mentioning
confidence: 89%